A New Simplified Prediction Method of the Contact State between Shallow Foundations and Swelling Ground - Farid, Z.; Lamdouar, N.; Bouziyane, J. Ben (Civil Engineering Journal, 2021)
Prediction of the contact state between soil and structure is a key step in any study of shallow foundations resting on swelling soil. However, in practice, the foundation designer has no simple and rapid method, at the design stage, to define the contact conditions. This study presents a new method, both simple and reliable, to predict the contact state. To do this, a soil-structure interaction model is developed. The building behavior is investigated with the Eulerâ€“Bernoulli beam theory and the ground behavior is investigated with a Winkler model. The soil-structure interaction is then, studied at the equilibrium state. The thereby obtained equation is analyzed and all of its parameters are synthesized in a new factor named "Detachment Factor". The decidability of the contact is thus reduced to the study of this single element, which allows a reasonable approach to the knowledge of the surface rate engaged in the shallow footings - expansive soil interactions. The conclusions of the current study are validated against five cases treated in the literature in various regions around the world. In addition, a parametric study of the â€œDetachment Factorâ€ shows that each of its parameters (i.e. swelling stiffness, shape of initial soil surface, permissible deflection, structure geometry and loads) has a variable effect on the contact state between a footing and swelling ground. But, the structure load has the most significant effect on it.Â Doi: 10.28991/cej-2021-03091697 Full Text: PDF